Diseño y construcción de una máquina CNC para corte de poliestireno expandido por hilo caliente de 2500 mm de longitud con recorrido de 2600 mm en eje X y 1300 mm en eje Y - Castillo Briceño, Juan Carlos (2018)
In the national market, for the elaboration of expanded polystyrene products with added value it is necessary to use automated cutting machines, acquirable only by importation and with high costs, hence the purpose of the present project consisted of designing and building a machine of automated cutting by CNC technology with a more affordable cost to be implemented in a microenterprise in the city of Quito. To establish the technical requirements, the employment situation of this type of machines in our country was evaluated, so two local companies were visited in order to obtain relevant information. It was complemented by the selection of a foreign machine alternative to facilitate the choice of transmission, guidance and movement generation systems. The design focuses on the calculation of structural elements, bolted and welded joints and the selection of transmission and displacement components. After cost analysis and profitability indicators, the construction of the machine was carried out through traditional manufacturing processes. During the testing phase, 26 and 30 AWG gauge cutting wires were used to determine the most suitable conditions for cutting. The most important results indicate an average safety factor of 22,34 in its structural elements, use of 98% of national materials and components for a final machine cost of $ 2822,99 and the appropriate cutting conditions with a current of 2, 3 Amps (175 ° C) and an average cutting speed of 475 mm / min.